Water and Society: Interdisciplinary Education in Natural Resources. (August 2016) - Kulcsar, Laszlo J.; Aistrup, Joseph A.; Bulatewicz, Thomas; Peterson, Jeffrey M.; Welch, Stephen M.; Steward, David R.
Abstract: Natural resource management and education must account for both the natural and human components of a complex system, yet examples of such interdisciplinary approaches are still relatively rare, especially in education. This study discusses a graduate seminar on water management, developed from an interdisciplinary National Science Foundation (NSF) grant. The seminar applied constructivist pedagogy which is not only best suited for interdisciplinary work, but also allows flexibility to redesign the course components and deliverables after each evaluation cycle. While the seminar was a successful experiment, several challenges remain when implementing such courses. These challenges include not only the organization and assessment of course deliverables, but also fitting such courses into the administrative structure of the university when represented disciplines are located in several colleges across campus.